Psychosocial impact of surgical complications and the coping mechanisms among surgeons in Uganda and Eastern Democratic Republic of the Congo. - Franck Katembo Sikakulya; Joshua Muhumuza; Bives Mutume Nzanzu Vivalya; Simon Binezero Mambo; Larrey Kasereka Kamabu; John Kasereka Muteke; Justin Paluku Lussy; Michel Kalongo Ilumbulumbu; Tapem Emmanuel; Sonye Magugu Kiyaka; Alpha Kavuyiro; Claude Mukandirwa; et al. (Public Library of Science (PLoS), 2024)
We aimed to assess the psychosocial impact from postoperative complications on the surgical workforce and the coping mechanisms they use following these complications in Uganda and Eastern Democratic Republic of the Congo (DRC). This was a cross-sectional multi-center study conducted from first February 2022 to 31st March 2022 in the preselected main teaching hospitals of Uganda and Eastern DRC. We surveyed the surgical workforce (practicing surgeons, Obstetrician-Gynecologists, and residents in surgery/ Obstetrics-Gynecology) who had experienced postoperative complications in their career. Data was analysed using SPSS version 23. One hundred ninety-eight participants responded to the questionnaire. Worry about patient and reputation were the commonest psychological impacts in 54.0% and 45.5% of the participants respectively. Majority of the participants (55.1%) used positive coping mechanisms with a positive impact on their practice (94.4%). Being a female doctor (AOR = 2.637, CI 1.065-6.533, P = 0.036), worrying about reputation (AOR = 3.057, CI = 1.573-5.939, P = 0.001) and guilt after a complication (AOR = 4.417, CI = 2.253-8.659, P = <0.001) were predictors of a negative coping mechanism. Postoperative surgical complications continue to cause a huge psychological impact on the operating doctors in Uganda and the Eastern DRC. Female doctors, those that worry about the reputation and those that feel guilty following a complication should be given more support and guidance by peers when surgical complications occur to their patients.